KALIGRAFI ARAB TENTANG KEJADIAN MANUSIA MENURUT AL-QURAN DALAM KARYA SENI GRAFIS (STENCIL PRINT) - Eli Rosmita, Drs. Syafei, M.Ag. (Universitas Negeri Padang, 2019)
This Final Project aims to convey information to the public about how the process of human creation according to the Al-Quran through verbal language by visualizing verses about human events according to the Al-Quran through Arabic calligraphy (stencil print). which is expected to add knowledge the community and will know about this, not make a proud and arrogant person because remember how their process was created. The method in making this work, through several stages, namely: (1) Preparation, (2) Elaboration, (3) Synthesis, (4) Realization concepts and (5) Resolutions are then exhibited. Ten works were presented for the following: Marriage, Fertilization, Nutfa, Alaqah, Madghah, Izam and lahm, Nasyah, Nafikha-Ar Ruh, Birth.Kata kunci : Arabic caligraphy, human event , Stencil Print.